Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.6 - Factoring Trinomials - Exercise Set: 66

Answer

$(x-9)(4x-3)$

Work Step by Step

The two numbers whose product is $ac= 4(27)=108 $ and whose sum is $b= -39 $ are $\{ -36,-3 \}$. Using these two numbers to decompose the middle term, then the factored form of the expression, $ 4x^2-39x+27 $, is \begin{array}{l}\require{cancel} 4x^2-36x-3x+27 \\\\= (4x^2-36x)-(3x-27) \\\\= 4x(x-9)-3(x-9) \\\\= (x-9)(4x-3) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.